Knowledge Sharing dalam Ekosistem UMKM: Perspektif Pelaku Usaha di Kota Padang - Chichi Andriani; Yunia Wardi; Susi Evanita; Hendrik Heri Sandi (Universitas Negeri Padang, 2025)
This study aims to examine the perceptions of Micro, Small, and Medium Enterprises (MSMEs) towards knowledge sharing practices in Padang City. The research approach used is causal-quantitative, with primary data collection through distributing questionnaires to 90 MSME respondents. To support the empirical analysis, this study is also supplemented with secondary data through a systematic literature study of 12 relevant scientific articles, published between 2004 and 2024, and obtained from the Google Scholar and ScienceDirect databases. The results of the analysis show that the average Total Composite Rating (TCR) score for knowledge sharing practices is at 75.19%, which is included in the